El desvanecimiento de lo popular. Gentrificación en el Centro Histórico de la Ciudad de México, de Vicente Moctezuma Mendoza - Camarena Luhrs, Margarita (El Colegio de México A.C., 2023)
This book is enriching because it contributes to the debate and understanding of urban inequalities. This innovative book can be purchased in print or in its digital edition.